The Illinois detective agency : [large type] the case of the missing cattle - Wolfe, Ethan J. (Wheeler Publishing Large Print Western, 2021)
"N 1884, the founder and matriarch of the Illinois Detective Agency is now elderly and active in the way that "Charlie" of Charlie's Angels was. Founded in 1848 as a stock detective agency, the founder is still the backbone of the business he built from the ground up. In The Case of the Missing Cattle, the Stock Growers Association of Montana appeals to Porter for help with a major cattle theft problem inside the Montana Territory. Hundreds, maybe even thousands of cattle are being stolen off the open ranges, and the local sheriffs and army outposts are helpless to stop it. Porter assigns two of his best agents to the case, James Duffy and Jack Cavill. Both are experts in forensics of the day, expert marksmen, superior detectives, and fearless"--"--